1993
DOI: 10.2307/3431467
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the Food-Borne Carcinogens 2-Amino-3-Methylimidazo-[4,5-f]quinoline and 2-Amino-3,8-Dimethylimidazo[4,5-f]-Quinoxaline in the Rat As a Model for Human Biomonitoring

Abstract: Metabolism of 2-amino-3-methylimidazD[4,5-Jlquinoline (IQ) and 2-amino-3-dimethylimidazoll4,5-Jjquinoxaline (MeIQx) and their binding to blood proteins were examined in the rat to develop methods of human biomonitoring.Hemoglobin and serum albumin were among many blood proteins modified. Approximately 0.01% ofthe dose for both compounds was bound to these proteins, and induction ofcytochrome P450 with polychlorobiphenyls resulted in decreased levels of adduction. Hemoglobin sulfinic acid amide adducts could no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Liver cytochrome P450 in humans and rats is able to realize several hydroxylations of the IQ molecule, but never at position 7 (33). Furthermore, Rumney et al have clearly shown that this metabolite cannot be produced by feces of germfree rats, while it is always produced by feces of conventional or HMA rats (27).…”
Section: Discussionmentioning
confidence: 99%
“…Liver cytochrome P450 in humans and rats is able to realize several hydroxylations of the IQ molecule, but never at position 7 (33). Furthermore, Rumney et al have clearly shown that this metabolite cannot be produced by feces of germfree rats, while it is always produced by feces of conventional or HMA rats (27).…”
Section: Discussionmentioning
confidence: 99%